PBL On Line: A proposal for the organization, part-time monitoring and assessment of PBL group activities - Enric Marti; Antoni Gurguí; Debora Gil; Aura Hernández-Sabaté; Jaume Rocarias; Ferran Poveda (OmniaScience, 2015)
This report presents the organisation of PBL (Project Based Learning) for a subject included in the IT engineering degree course. It is the result of 10 years of experience of the implantation and continuous improvement of the PBL class structure. The latest innovations include the experience of part-time monitoring with PBL groups using the OpenMeetings tool in Moodle 2.0, the adoption of activities that improve learning and interdependence such as the jigsaw classroom, the clear definition of deliverables that students should present along the semester and the assessment criteria, both on groups and individuals. As a result of this experience, we present PBL student enrolment indexes, student assessment surveys and lecturers' opinions. We conclude with some topics for discussion about the PBL methodology.